Penerapan Metode Convolutional Neural Network pada Sistem Klasifikasi Penyakit Tanaman Apel berdasarkan Citra Daun - Pamungkas, Nicholas Bagus; Suhendar, Agus (Jurnal Pendidikan Informatika (EDUMATIC), 2024)
Apple leaf diseases can cause significant crop failure and impact the economy of farmers and the agricultural industry. With the increasing demand for quality apples, it is important to develop effective and efficient solutions to detect apple plant diseases early. This research aims to develop an automated system that can identify diseases in apple plants based on leaf images using the Convolutional Neural Network (CNN) model. This model was developed with the ResNet50V2 architecture to classify four leaf conditions: three types of common diseases and one healthy condition. This research applies the CNN model for leaf image processing and the Waterfall system development method. The stages start from needs analysis by collecting data to be processed by the cnn model, interface design of the classification system, program code implementation, and functionality testing using black-box testing. CNN model development includes the stages of collecting datasets sourced from Malang apple plantations as many as 150 images and Kaggle public datasets totalling 3,071 images, then image preprocessing, model development and training. Our research results produced an apple plant disease classification system by implementing the CNN model. Based on the results of testing the system and the model used, it shows that the CNN model applied in the system achieves a classification accuracy of 99.01%, and the functionality of the system built runs well.